Decision Support System for Evaluation of Peatland Agroecology Suitability in Pineapple Plants - Putra, Fiqhri Mulianda; Sitanggang, Imas Sukaesih; Sobir, Sobir (Scientific Journal of Informatics, 2020)
A Pineapple (Ananas comosus (L.) Merr.) It is one of the leading commodities in the Indonesian horticultural sub-sector. Based on data from PDSIP in the last 5 years the development of pineapple production has increased but not too high as well as the harvested area. One of the areas that cultivate pineapple plants in Riau Province is Kampar Regency. Its production in 2015 was 8,482 tons, down from 20,046 tons in 2013. However, this amount is not optimal considering the area in Kampar Regency is still large enough for pineapple cultivation. Kampar District has a potential peatland of around 191,363 ha. About half of the area is thin peat, while the rest varies from moderate to deep peat. The success or failure of peatland management for cultivated land is highly dependent on the condition of its characteristics and the mastery and scientific understanding of the character of peat. This shows the need to evaluate the carrying capacity of land-based on its suitability so that it can be used as a guide in wise land-use planning. This study aims to create a fuzzy inference system model with Mamdani method in determining the agroecological suitability of peatlands for pineapple plants, this is due to the target class of land suitability parameters based on FAO provisions, namely S1, S2, S3, and N. Based on the obtained model, decision support systems will be developed for the suitability of peatland agroecology for pineapple plants.